Exfoliation of Na2Ti3O7 into Colloidal Nanosheets with Enhanced Discharge Capacity. (10th August 2020) - Lee, Won‐Jae; Lee, Minseop; Paek, Seung‐Min
Abstract : Sodium‐ion batteries (SIBs), which are being considered as possible alternatives to lithium‐ion batteries, have attracted great scientific and industrial interest because sodium is inexpensive and more abundant than lithium. Among various anode materials for SIBs, Na2 Ti3 O7, with a layered structure, has a high potential due to its stable electrochemical sodiation/desodiation behavior. However, Na2 Ti3 O7 has a large band‐gap energy and a zigzag framework, which results in low electrical conductivity and poor sodium‐ion diffusion. Thus, to circumvent such drawbacks, in this study, Na2 Ti3 O7 was successfully exfoliated by the soft‐chemical exfoliation technique via a two‐step intercalation reaction. Transmission electron microscopy (TEM) studies show that the obtained exfoliated material is composed of thin nanosheets. Electrochemical sodium‐ion storage tests showed that the exfoliated nanosheets had a much higher discharge capacity than bare bulk Na2 Ti3 O7, revealing that the exfoliation process could be utilized to develop new electrode materials with enhanced energy‐storage properties. Abstract : Exfoliation of Na2 Ti3 O7 into colloidal nanosheet.